Sugar as a Biofuel Implications for Philippine Agriculture and Food Security - Rodriguez, U-Primo E.; Cabanilla, Liborio S. (2008)
This paper examines the economic impacts of using sugar as feedstock for biofuels on agricultureand food security in the Philippines. In particular, it focuses on the impacts on prices, outputs, con-sumption and trade of industries in the agricultural and food processing sectors. The tool used in thestudy is computable general equilibrium model of the Philippines. The analysis was implemented byreplacing inputs with crude petroleum with bioethanol, which is sourced from the sugar industry, in thepetroleum refining industry. The study found that the initiative raises the output of the 'Agriculture, Fishery and Forestrysector'. However, this is driven mostly by the expansion of the output of the sugar industry, with a largeproportion of the industries in the sector experiencing a contraction in output. The analysis also showsthat promoting sugar as a biofuel feedstock can have adverse effects on food security. This conclusionis drawn mainly from the projected decline in the consumption of products from the agricultural andfood processing sectors. © Published by the College of Agriculture.
Keywords: Sugar; Biofuels